Diosbulbin C, a novel active ingredient in Dioscorea bulbifera L. extract, inhibits lung cancer cell proliferation by inducing G0/G1 phase cell cycle arrest - Zhiyu Zhu; Yanfen Liu; Jiangping Zeng; Shuyi Ren; Lu Wei; Fei Wang; Xiaoyu Sun; Yufei Huang; Haiyang Jiang; Xinbing Sui; Weiwei Jin; Lijun Jin; et al. (BMC, 2023)
Abstract Background Despite the critical progress of non-small cell lung cancer (NSCLC) therapeutic approaches, the clinical outcomes remain considerably poor. The requirement of developing novel therapeutic interventions is still urgent. In this study, we showed for the first time that diosbulbin C, a natural diterpene lactone component extracted from traditional Chinese medicine Dioscorea bulbifera L., possesses high anticancer activity in NSCLC. Methods A549 and NCI-H1299 cells were used. The inhibitory effects of the diosbulbin C on NSCLC cell proliferation were evaluated using cytotoxicity, clone formation, EdU assay, and flow cytometry. Network pharmacology methods were used to explore the targets through which the diosbulbin C inhibited NSCLC cell proliferation. Molecular docking, qRT-PCR, and western blotting were used to validate the molecular targets and regulated molecules of diosbulbin C in NSCLC. Results Diosbulbin C treatment in NSCLC cells results in a remarkable reduction in cell proliferation and induces significant G0/G1 phase cell cycle arrest. AKT1, DHFR, and TYMS were identified as the potential targets of diosbulbin C. Diosbulbin C may inhibit NSCLC cell proliferation by downregulating the expression/activation of AKT, DHFR, and TYMS. In addition, diosbulbin C was predicted to exhibit high drug-likeness properties with good water solubility and intestinal absorption, highlighting its potential value in the discovery and development of anti-lung cancer drugs. Conclusions Diosbulbin C induces cell cycle arrest and inhibits the proliferation of NSCLC cells, possibly by downregulating the expression/activation of AKT, DHFR, and TYMS.